2012
DOI: 10.1016/j.jcrs.2011.11.040
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral refraction in pseudophakic eyes measured by infrared scanning photoretinoscopy

Abstract: No author has a financial or proprietary interest in any material or method mentioned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Others have shown relative myopia in the vertical meridian regardless of central refractive error. 13,25 …”
mentioning
confidence: 99%
“…Others have shown relative myopia in the vertical meridian regardless of central refractive error. 13,25 …”
mentioning
confidence: 99%
“…There is some evidence [21,22] indicating that current IOLs do not provide peripheral image quality as good as that of the natural crystalline lens. Being designed specifically around surgical technique and aiming to restore emmetropia on the optical axis, IOLs are associated with increased astigmatism and higher order aberrations at the periphery of the visual field of the pseudophakic eye.…”
Section: Introductionmentioning
confidence: 99%
“…revious clinical studies and computational modeling have shown that the retinal image in the peripheral visual field differs in pseudophakic eyes than in phakic eyes. [1][2][3][4][5][6][7][8] Recent studies found that the peripheral retinal image quality is degraded in pseudophakic patients and peripheral image degradation can affect visual function. 1,9 Reduced contrast and image quality in the periphery of the visual field could also affect diagnostic and imaging procedures in pseudophakic eyes, such as wide-field retinal imaging or visual field testing.…”
mentioning
confidence: 99%